2021
DOI: 10.1177/1069072720976620
|View full text |Cite
|
Sign up to set email alerts
|

Testing Psychology of Working Theory Among Spanish-Speaking Latinx Workers in the U.S.

Abstract: Psychology of Working Theory (PWT) has recently gained empirical support; however, its assumptions have yet to be tested for cultural responsiveness in Latinx communities, one of the fastest-growing worker populations in the U.S. The current study had two major aims: (a) to translate and validate instruments measuring PWT constructs from English into Spanish, and (b) to test theorized PWT predictors of decent work in a sample of Latinx workers ( N = 287). First, we translated and validated instruments measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…PWT has been studied mostly with college students and working adults, with existing research affirming the negative relationship of economic constraints and marginalization with decent work and the positive contributions of work volition and career adaptability to decent work (Duffy et al, 2020). Existing research also supports the usefulness and cultural responsiveness of the PWT model for Latinx adults in the workforce (Autin et al, 2021), but has not been fully assessed with Latinx youth to date. The extension of PWT with adolescents is important, as young people are already engaging in decision-making about their future educational and career goals and taking steps toward those goals (Lapan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…PWT has been studied mostly with college students and working adults, with existing research affirming the negative relationship of economic constraints and marginalization with decent work and the positive contributions of work volition and career adaptability to decent work (Duffy et al, 2020). Existing research also supports the usefulness and cultural responsiveness of the PWT model for Latinx adults in the workforce (Autin et al, 2021), but has not been fully assessed with Latinx youth to date. The extension of PWT with adolescents is important, as young people are already engaging in decision-making about their future educational and career goals and taking steps toward those goals (Lapan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the psychological perspective underlying these two instruments is conducive to linking with other psychological concepts or conceptual frameworks. The decent work notion developed by Duffy, which was informed by the psychology of working theory, has been given a broad psychosocial perspective and has sparked a keen academic interest in studying the influence of decent work in organizational contexts (Duffy et al, 2019 ; Autin et al, 2021 ). Ferraro's decent work notion which highlights individuals' perceptions of work by referring to the ILO's 11 substantive elements, has also been studied in conjunction with a wide variety of psychological phenomena, such as personal burnout, work engagement, thriving at work, and motivation, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The social recognition Second, the decent work scale incorporated with a social recognition component enhances the capacity of the psychology of working theory for enabling people to improve their wellbeing and self-fulfillment in organizational contexts. The power of the psychology of working theory to promote the individual agency of workers in organizational contexts has been supported by empirical data in various studies (Duffy et al, 2020;Kim et al, 2020;Autin et al, 2021;Masdonati et al, 2021), yet the capacity of the theory is still undermined with respect to promoting the shared agency among workers and informing the development of relevant management practices and policies due to a weak link with an interpersonal perspective. As there are still so many political and socioeconomic barriers such as marginalization and discrimination affecting a large segment of population's access to decent work, Blustein et al (2019) suggested that expanding the decent work notion and enhancing the inclusiveness of the concept by incorporating new perspectives into the psychology of working theory are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a decent work notion incorporated with a social recognition component is aligned with the purpose to strengthen the epistemological ground underlying the psychology of working theory in relation to enhancing positive self-concepts for constructing meaning in work. Conceptually, the psychology of working theory takes social and economic constraints faced by people such as discrimination and marginalization encountered in the workplace as an important area for reform, suggesting that these constraints suffered by people are jeopardizing their development of psychological resources and depriving their access to decent work, which will further harm their satisfaction of needs, and achievement of wellbeing and self-fulfillment ( Blustein et al, 2016 , 2019 ; Duffy et al, 2016 , 2019b ; Pires et al, 2020 ; Autin et al, 2021 ; Masdonati et al, 2021 ). Access to decent work in both structural and dynamic senses is perceived by the psychology of working theory as the key mechanism for counteracting the negative effects caused by different sources of individual and social constraints on people’s wellbeing and self-fulfillment, as decent work is expected to provide some psychological conditions such as a sense of security or stability which are indispensable for cultivating workers’ positive self-concepts and satisfying their essential needs for survival, social connection, and self-determination ( Blustein, 2013 ; Blustein et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%